Nutritional status of animals in peri-urban dairy complexes in Punjab, India - BAKSHI, M P S; WADHWA, M; HUNDAL, J S (The Indian Journal of Animal Sciences, 2010)
The study was taken up to assess the nutritional status of dairy animals in peri-urban dairy complexes in Punjab, India. About 24 to 29 dairy houses were selected randomly from each of Ludhiana (LDC), Amritsar (ADC), Jalandhar (JDC), Ferozepur (FDC) and Hoshiarpur (HDC) peri-urban dairy complexes. Buffaloes predominated in almost all peri-urban dairies, except in FDC. The animals of FDC had the lowest (P<0.05) and that of LDC had the highest body weight (478 vs. 572 kg). The milk yield of the animals of LDC was highest (P<0.05), while that of ADC was the lowest (9.65 vs. 5.96 kg/animal/day). The space allocated per adult cattle unit was highest in JDC and lowest in LDC, which was only 42 to 55% of the recommended area of 11.25 m2/adult cattle unit. Wheat bran was the most common feedstuffs used in the rations of lactating animals. Non-conventional feed resources like pulses chunni, brewery and starch industry waste played a significant role in peri-urban dairy production system. The CP and EE content in the diet of animals was less than the recommended level to the extent of 28 and 30%, 17 and 32%, 22 and 38%, 13 and 26%, 12 and 4% respectively in JDC, ADC, FDC, LDC and HDC. The NDF content in complete feed was 114 to 144% higher than the recommend level of >28%. The milk urea nitrogen (MUN) was lowest (P<0.05) in animals of FDC (8.1mg/dl) and highest in animals of HDC (20.8mg/dl). About 24, 14, 64, 83 and 50% of the dairy houses of JDC, ADC, FDC, LDC and HDC, respectively, offered DM less than the requirement. The daily consumption of nutrients was over and above the requirements in JDC, ADC and HDC, but less (P<0.05) than the requirement in LDC (22% DM, 18%CP, 15%DCP and 21%TDN) and FDC (5%DM, 8%CP, 11%DCP and 7%TDN). Only 3.6% of the dairy houses of FDC and 25% of the dairy houses of LDC offered mineral mixture to their animals, while mineral mixture was not offered at all in JDC, ADC and HDC. It was concluded that CP and EE content in the diet of the animals was less than the recommended levels in all the peri-urban dairy complexes in Punjab, but the daily consumption of nutrients was less than the requirements, only in LDC and FDC. The farmers need to be motivated to feed nutritionally balanced diet.